Hubungan Status Gizi Ibu Saat Hamil dengan Status Gizi Pada Anak Usia 1-3 Tahun di Wilayah Kerja Puskesmas Kotabunan - Mokodompis, Salsabila; Rompas, Sefti Selfijani Jehermia; Meo, Maria Lupita Nena (Mapalus Nursing Science Journal, 2025)
Background: Nutritional status is the most important factor for the growth and development of children and is the end result of the balance of nutrients entering the body. The nutritional status of mothers during pregnancy has a significant impact on the growth and development of children. Children born to mothers who experience malnutrition and live in inadequate conditions have a higher risk of malnutrition. Objective This study aims to determine the relationship between maternal nutritional status during pregnancy and the nutritional status of children aged 1-3 years in the working area of the Kotabunan Community Health Center. Methods This study is a retrospective cohort study with a cross-sectional design and purposive sampling method. The instruments used for assessing maternal nutritional status are the Maternal and Child Health (KIA) book, and for assessing children's nutritional status, a digital weight scale and height meter were used. A total sample of 85 individuals was analyzed using Gamma statistical testing. Results  Based on statistical tests, a relationship was found between maternal nutritional status during pregnancy and the nutritional status of children aged 1-3 years in the working area of the Kotabunan Community Health Center, indicated by the following categories: weight-for-age (W/A) with a P value of 0.007, height-for-age (H/A) with a P value of 0.030, and weight-for-height (W/H) with a P value of 0.007. Conclusion The results show that the majority of maternal and child nutritional statuses in the Kotabunan Community Health Center area are normal, and there is a significant relationship between maternal nutritional status during pregnancy and the nutritional status of children aged 1-3 years. To improve and maintain normal nutritional status, health education regarding proper nutritional fulfillment can be provided.